Pendampingan Pencatatan Laporan Keuangan Sederhana pada Usaha Ternak Ayam Potong Broiler di Kota Tiakur - Thimotina Killay; Adonia A. Batkunde; Janet Wilsye Litualy; Engrith Grafelia Leunupun; Sitti Fatimah Kamaruddin; Lenci Madiuw; Dwi Kiswantini (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
This community service activity was carried out in a broiler chicken farming business located in the city of Tiakur, Southwest Maluku Regency. The purpose of this service to assist livestock entrepreneurs in strengthening MSME management, especially in accounting application, so that the financial reports producted comply with the applicable accounting principles based on SAK-EMKM (Financial Accounting Standars for Micro, Small, and Medium Enterprise). The method used in this activity is Action Research, in the form of assistance with financial report recording for all broiler chicken farming business operators in Tiakur, Southwest Maluku Regency. This activity provides new learning experiences for students, enchancing their knowledge and skills, as well offering motivation and innovation to the community. Additional, this activity also provides an understanding of financial report recording, such as balance sheets and income statemets, for broiler chicken farming businesses.